STUDIES ON THE POSTERIOR SILK GLAND OF THE SILKWORM, BOMBYX MORI : I. Growth of Posterior Silk Gland Cells and Biosynthesis of Fibroin During the Fifth Larval Instar - Tashiro, Yutaka (The Rockefeller University Press, 1968)
Growth of the posterior silk gland and biosynthesis of fibroin during the fifth larval instar of the silkworm, Bombyx mori, have been studied. In accordance with the exponential increase in the wet weight of the gland, the amounts of DNA, RNA, protein, and lipids per animal increased rapidly in the early stage of the fifth instar (0–96 hr). Biosynthesis of fibroin, on the contrary, mainly proceeds in the later stage of the fifth instar (120–192 hr). Electron microscopical observations have shown that, in the very early stage (0–12 hr), a number of free ribosomes exist in the cytoplasm. Rough endoplasmic reticulum (ER) with closely spaced cisternae was also observed. Then rough ER starts to proliferate rapidly, and at the same time lamellar ER is rapidly or gradually transformed into vesicular or tubular forms. In the later stage of the fifth instar (120–192 hr), the cytoplasm is mostly filled with tubular or vesicular ER. Golgi vacuoles, free vacuoles (fibroin globules), and mitochondria are also observed. It is concluded that in the early stage of the fifth instar the cellular structures necessary for the biosynthesis of fibroin are rapidly formed, while in the later stage the biosynthesis of fibroin proceeds at a maximum rate and utilizes these structures.